A comparison of two ship performance models against full-scale measurements on a cargo ship on the Northern Sea Route. (18th August 2021) - Li, Zhiyuan; Ryan, Christopher; Huang, Luofeng; Ding, Li; Ringsberg, Jonas W.; Thomas, Giles
ABSTRACT: The present paper introduces the development and verification of two ship performance models which have been implemented in a voyage planning tool designed for summer Arctic operations of commercial vessels. A novel ice resistance estimation algorithm for ice-floe conditions is implemented in the ship performance models. The fuel consumption predicted using both of the models are compared against full-scale measurements collected on a cargo ship of lower ice-class on the Northern Sea Route. This work found that both models meet the purpose of estimating ship fuel consumption for such a voyage planning tool and identified directions for future efforts. In addition, the typical transit scenarios in summer Arctic conditions presented in this study prove that a voyage planning tool with viable ship performance models facilitates Arctic shipping in a safe and sustainable way.